Khat distorts the prefrontal cortex histology and function of adult Wistar rats - Echoru, Isaac; Bukenya, E.M Edmund; Masilili, Godfrey; Owembabazi, Elna; Lemuel, Ann Monima; Ahimbisibwe, James (Anatomy Journal of Africa, 2018)
Khat is a psychoactive herbal drug of pronounced ethno-pharmacological significance often abused due to its unregulated use. It affects many brain centers including the prefrontal cortex which is the anterior most part of the frontal lobe. The prefrontal cortex modulates working memory, planning complex cognitive behaviors however; it is linked to many psychological disorders such as depression, schizophrenia and memory loss. We studied the effects exerted by khat on the PFC cytoarchitecture and functions since this part of the brain is highly interconnected with various cortical regions. This was an experimental study of 6 weeks. A total of 24 male adult wistar rats of 130g-155g were divided into four groups of 6 animals that received respective khat doses of 2000mg/kg, 1000mg/kg, 500mg/kg and 10ml/kg of distilled water for the controls. Brain to body weight ratio was determined at week 6 using an analytical balance (Fisher Science Education™, RS232C; USA). Histology of the brain was determined using H and E and Kulvers staining technique. Khat exhibited features of prefrontal cortex disorientation such as necrosis, vacuolations, chromatolysis, demyelination, cortical degeneration and hemorrhage in a dose dependent manner. Selective attention and working memory were impaired well as brain to body weight ratio was reduced significantly (P ≤ 0.05). Repeated exposure to khat distorts the prefrontal cortex cytoarchitecture and impairs selective attention and working memory accuracy due to ischemia and cell exhaustion by khat toxicity.
Keywords: Khat; Prefrontal cortex histology; Working memory; Selective attention